2020
DOI: 10.1111/lam.13409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different target genes for the detection of Salmonella sp. by loop‐mediated isothermal amplification

Abstract: This study evaluates six specific target regions in the salmonella genome using the loop-mediated isothermal amplification (LAMP) technique. Primers were designed targeting five regions, which had not previously been studied intensively, and the invA gene, which is frequently used in biomolecular detection of Salmonella spp.. Most primer sets were not able to amplify DNA of all tested salmonella strains, revealing deficiencies in inclusivity of the corresponding target regions. These findings highlight the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…Previous studies have identified gene markers, such as fimA , hilA , invA , and ttr , that are useful in detecting Salmonella species ( Laing et al, 2017 ; Gand M. et al, 2020b ; Kreitlow et al, 2021 ). Moreover, for serovar identification, gene markers based on allelic variations in O and H antigen genes were used ( Laing et al, 2017 ; Gand M. et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified gene markers, such as fimA , hilA , invA , and ttr , that are useful in detecting Salmonella species ( Laing et al, 2017 ; Gand M. et al, 2020b ; Kreitlow et al, 2021 ). Moreover, for serovar identification, gene markers based on allelic variations in O and H antigen genes were used ( Laing et al, 2017 ; Gand M. et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The serovar-specific primers were selected for the criterium of exclusivity based on the in silico comparative genome analysis, but their target genes do not necessarily represent specific virulence genes or O and H antigen associated markers. The assay also includes a primer set for the type III secretion system-associated invA, a widely used gene target to confirm the genus of Salmonella [13,18]. All strains included in the study signaled positive using the selected invA primers (Table 3).…”
Section: Evaluation Using Characterized Salmonella Isolatesmentioning
confidence: 99%
“…First LAMP assays to identify Salmonella spp. and a few serovars in clinical and food samples have been described in recent years [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In Salmonella, the invA gene is an invasive protein gene, encoding a protein that establishes the invasive ability of Salmonella to intestinal mucosal cells. Besides, this gene is the most direct indicator of pathogenic Salmonella existence (Villamil et al 2020;Kreitlow et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Kreitlow et al . 2021). Another alternative gene for detecting Salmonella is the fimY gene, which has been detailed as one of a kind to the Salmonella species and regulates type 1 fimbrial expression (Tinker and Clegg 2000).…”
Section: Introductionmentioning
confidence: 99%